MENGHADIRKAN PEMERINTAHAN UNTUK WARGA - Ari Surida (GOVERNABILITAS (Jurnal Ilmu Pemerintahan Semesta), 2022)
This study examines the village government which has always been used as an object before the Law Number 6 of 2014 concerning Villages. The questions posed in this study were to what extent the village head was placed as a village leader and how the village head became an independent village head. The method used in this research is qualitative with research data collected by observation, documentation, and in-depth interviews. The analysis of this research uses content analysis as a new path from the tradition of positivism and postmodernism. The results showed that the Sriharjo Village Head was transforming from government as an object to village government as an independent subject in carrying out village development.